Understanding behavioural intention to play online game: The case of VocBlast - Zuraina, Ali (IOP Publishing, 2018)
Research has shown that mobile learning enables its users to learn at any time and place. The current study investigates the use of VocBlast; an app that integrates technical and engineering vocabulary, in terms of understanding the behavioural intention of its players. The study employs 129 engineering and technical students from Universiti Malaysia Pahang (UMP). Online survey was used to collect their opinions; in particular male and female students' opinions on the use of the app in the future. The results of the study indicated that there was no significant difference pertaining to their behavioural intention using VocBlast in the course of time. The study implies that more time needs to be given to the students in playing VocBlast as it is believed that playing the game repetitively would promote positive perceptions among its players.